2004
DOI: 10.1002/rcm.1733
|View full text |Cite
|
Sign up to set email alerts
|

Coupling of fully automated chip electrospray to Fourier transform ion cyclotron resonance mass spectrometry for high‐performance glycoscreening and sequencing

Abstract: The NanoMate robot has been coupled to a Fourier transform ion cyclotron resonance (FTICR) mass spectrometer at 9.4 T and implemented for the first time for complex carbohydrate analysis. It was optimized in the negative ion mode to achieve automated sample delivery on the chip along with increased sensitivity, ultra-high resolution and accurate mass determination. A novel bracket has been designed to allow a reliable mounting of the NanoMate to the Apollo electrospray ionization (ESI) source of an APEX II ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
44
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 41 publications
1
44
0
Order By: Relevance
“…The highest sensitivity obtained in this set of experiments was 0.5 pmol/ mL, which represents a value with one order of magnitude higher than the one achieved in a similar study carried out by using capillary ESI infusion in the same Apollo Apex II configuration [32]. For the initiation of the chip spray, the fine tuning on the x-, y-, and z-axes of the chip nozzle toward the FTICR-MS inlet has been reported to be a critical step [50]. In addition, it was shown that a significant [61,62].…”
Section: Complex Biological Mixtures Of Glycopeptidesmentioning
confidence: 56%
See 4 more Smart Citations
“…The highest sensitivity obtained in this set of experiments was 0.5 pmol/ mL, which represents a value with one order of magnitude higher than the one achieved in a similar study carried out by using capillary ESI infusion in the same Apollo Apex II configuration [32]. For the initiation of the chip spray, the fine tuning on the x-, y-, and z-axes of the chip nozzle toward the FTICR-MS inlet has been reported to be a critical step [50]. In addition, it was shown that a significant [61,62].…”
Section: Complex Biological Mixtures Of Glycopeptidesmentioning
confidence: 56%
“…Recently, the first coupling of the NanoMate robot to the FTICR-MS at 9.4 T and sustained off-resonance CID (SORI CID) MS/ MS was reported [50]. The new assembly was optimized in the negative ion mode to combine automated sample delivery on the chip along with maximal sensitivity, ultrahigh-resolution, accurate mass determination provided by the FTICR instrument, and efficient MS/MS in one system.…”
Section: Coupling Of the Fully Automated Chip-based Nanoesi System Tomentioning
confidence: 99%
See 3 more Smart Citations